Delayed CTP-Derived Deep Venous Outflow: A Novel Predictor of Striatocapsular Infarction after M1 Thrombectomy - Peretz, S.; Pardo, K.; Naftali, J.; Findler, M.; Raphaeli, G.; Barnea, R.; Khasminsky, V.; Auriel, E. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Isolated striatocapsular infarction occurs commonly in patients with ischemic stroke following M1 thrombectomy. We aimed to explore the correlation between CTP-derived parameters of deep venous outflow at presentation and subsequent striatocapsular infarction in a retrospective cohort of such patients.MATERIALS AND METHODS: TTP and peak enhancement were measured on CTP-derived time-attenuation curves of the internal cerebral and thalamostriate veins bilaterally. The difference in TTP (ΔTTP) and the relative decrease in venous enhancement between the ischemic and normal sides were calculated. NCCT performed 24 (SD, 12) hours postthrombectomy was used to determine tissue fate in the caudate head, caudate body, lentiform nucleus, and internal capsule. Striatocapsular ischemia (striatocapsular infarction–positive) was defined as infarction and striatocapsular injury as either infarction, contrast enhancement, or hemorrhagic transformation in ≥1 of these regions. A striatocapsular ischemia score was calculated (0 = no ischemic region, 1 = 1 ischemic region, 2 = ≥2 ischemic regions).RESULTS: One hundred sixteen patients were included in the analysis. Sixty-one patients had striatocapsular infarction (striatocapsular infarction–positive). The mean thalamostriate ΔTTP was 1.95 (SD, 1.9) seconds for patients positive for striatocapsular infarction and 0.79 (SD, 2.1) for patients negative for it (P = .010). Results were similar for striatocapsular injury. The mean thalamostriate ΔTTP was 0.79 (SD, 2.1), 1.68 (SD, 1.4), and 2.05 (SD, 2) for striatocapsular infarction scores of 0, 1, and 2, respectively (P = .030).CONCLUSIONS: CTP-derived thalamostriate ΔTTP is an excellent surrogate marker for striatocapsular infarction in patients post-M1 thrombectomy. The novel approach of extracting venous outflow parameters from CTP has numerous potential applications and should be further explored.DTdistance from the carotid T to the thrombusICCintraclass correlation coefficientIVTintravenous thrombolyticLSAslenticulostriate arteriesSCAs+ASPECTS-based striatocapsular involvementSCIstriatocapsular infarctionSCInjstriatocapsular injurySCIsstriatocapsular ischemia score